Endowments, Output, and the Bias of Directed Innovation - BLUM, BERNARDO S. (Review of Economic Studies, 2010)
In this paper, I ask the question: Does the output-mix of countries change in response to changes in factor endowments? If so: How long does it take? Using data on capital, as well as skilled and unskilled labour employed in three-digit International Standard Industrial Classification (ISIC) manufacturing industries for a sample of 27 developing and developed countries over the 1973–1990 period, I find that the output-mix of countries does not change in response to endowment changes, even after 15 years. This answer raises another question: How then do countries absorb changes in factor endowments? The data show that in both the short and long runs, an increase in the supply of a production factor reduces its rate of return and makes it more intensively used in all sectors of the economy: changes in production techniques. In the long run, the point estimate is that the reduction in the rate of return is more than 50% larger than in the short run. This is consistent with induced innovations being predominantly biased towards the scarce factor.